A novel hydrogel orthotopic injection model in moderately hypofractionated radiation therapy for prostate cancer: Adaptive degradation and durable imaging - Yu, Hao; Wang, Cheng; Wu, Lingyun; Zhou, Ziyang; Wang, Yiqi; Li, Wenxiang; Yuan, Huili; Lu, Zeyi; Yan, Danfang; Chen, Si; Wang, Xu; Yan, Senxiang (Frontiers in Oncology, 2023)
Purpose Moderately hypofractionated radiotherapy (MHRT) holds an important position in prostate cancer management. Existing hydrogel spacers can protect the rectum from radiation damage, but need improvement. We explored the application of a novel hydrogel in MHRT with adaptive degradation and durable imaging functions. Methods and materials The hydrogels were irradiated with 6MV x-ray to detect the radio-resistance property. Male SD rats (n=45) underwent hydrogel injection between the prostate and rectum. CT was used for investigating the novel spacer’s degradation and imaging functions over three months. The hydrogel’s radiation-attenuation properties and biocompatibility were further assessed. Results Hydrogel weight and volume remained stable for six weeks post-injection. After MHRT ended, the hydrogel showed accelerated degradation characteristics and remained in the body for at most three months. CT values of hydrogels exceeded 300 Hounsfield units (HU) throughout treatment, significantly higher than in surrounding normal tissues. A significant dose drop behind the hydrogel was observed post-implantation. Biocompatibility tests of hydrogel found it safe enough for living organisms. Conclusions The novel hydrogel application was fully adaptable to prostate cancer MHRT modalities, largely stable during treatment, rapidly degraded after radiotherapy ended, and consistently maintained superior imaging performance and biocompatibility. This novel spacer will be an effective tool in the era of hypofractionated radiotherapy.